Improving Standards of Research Reporting in Intervention Research: Considerations for the Rehabilitation Treatment Specification System Model. - Reynolds, Stacey (American Journal of Occupational Therapy)
Replication and application of research in clinical practice require that interventions be described in detail by the producers of that research. Lack of treatment specificity in publications is thought to contribute to the nearly 17-yr gap between the publication and clinical implementation of best practices. In this editorial I explore a means of addressing this problem in the Rehabilitation Treatment Specification System (RTSS) and present an application of the RTSS to sensory integration intervention. The interprofessional Rehabilitation Treatment Specification System (RTSS) has great potential for reporting in a way that helps bridge the gap between research and practice, and while there are challenges to its implementation and widespread adoption that are currently being addressed, the American Journal of Occupational Therapy encourages authors to consider using RTSS components when describing rehabilitation interventions.